State of the Art and Future Directions of Healthcare 4.0: A Systematic Literature Review - Carlos Henrique dos Santos; Andre Luiz Romano; Walther Azzolini Junior; Francisco Ignacio Giocondo Cesar; Fabio Ferraco; Ivanhoe Rozo-Rojas (IEEE Access)
This article explores the emerging field of Healthcare 4.0, which integrates advanced technologies from Industry 4.0 to enhance decision-making processes in the healthcare context. As the healthcare landscape evolves, there is a pressing need to understand how these innovations can support clinical and operational management, ultimately improving patient outcomes and healthcare efficiency. This study employs a systematic literature review (SLR) methodology to investigate the current state of research on Healthcare 4.0 solutions, focusing on their applications across various healthcare sectors. The main scientific databases were considered and we evaluated peer-reviewed articles published in scientific journals until July 2024. The review identifies key themes, trends, and gaps in the literature, revealing that while the field is still in its infancy, there is a notable increase in publications, indicating growing interest and potential for future research. The findings categorize applications into several areas, including hospital general facilities and specific environments, highlighting the diverse contexts in which Healthcare 4.0 technologies are being implemented. Additionally, the study examines the geographical distribution of research, with a significant emphasis on developments in Asia and Europe. Regarding the decision objectives, we highlight the use of Healthcare 4.0 solutions to improve the performance of activities related to data exchange, diagnosis, and patient monitoring. Furthermore, considering the main techniques and tools adopted by the authors, Artificial Intelligence, Internet of Things, and Blockchain stand out, as well as hybrid approaches which integrate different solutions. By synthesizing these insights, the article contributes to a deeper understanding of how Healthcare 4.0 can transform decision-making in health facilities, offering directions for future research and practical implications for healthcare researchers and professionals.